Von Hippel-Lindau Disease and Pheochromocytoma - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
Nineteen percent of 82 unselected patients with pheochromocytoma studied at the University of Freiburg, Germany, and the University of California, San Diego, were found to be gene carriers of von Hippel-Lindau disease.